Analysis of electromagnetic energy harvester for various length of beam - Muhammad Izzuddin, Masrom (2012)
Energy harvesting is presented by the conversion of ambient mechanical energy into usable electrical energy. Compared with energy stored in such as batteries which is common storage elements, the environments represent a relatively inexhaustible source. In this study, there are two objectives that need to achieve. The first objective is to design an electromechanical energy harvester based on beam structure and analysis the effect of various length of beams to the voltage produced by the energy harvester. For the scope of research in this study is to see the relationship between frequencies and the amount of electricity produced, design a small size of energy harvester, beams are limited 3 length and outputs are presented on LCD and computer based. In this study, energy harvesting from the electromagnetic that produce magnetic field converts mechanical energy to electrical energy. Based on basic operating principles, magnetic flux produced when there are movements of the magnet through the coils. In this study, fabricate an electromagnetic energy harvester is the first step and make the experiment for three different length which is 9 cm, 11 cm and 13 cm. Frequency that use during experiment in range 100 Hz to 500 Hz. Result from the experiment are 9 cm (0.614211 V), 11 cm (0.69845 V) and 13 cm (0.915395 V). For the conclusion, this experiment succesfully achieve the main objective of this project study. To design an electromechanical energy harvester based on beam structure and make analysis about the effect of various length of cantilever beams to the voltage produced by the energy harvester. Important recommendation in this study is the range of the frequency should used frequency in range 10 Hz until 50 Hz, scaling down the dimensions of the proposed structure and to see its feasibility to be used in very lowpower micro systems, the mass of the coil should be large as possible within the available volume of the device to generate higher amount of voltage and make a simulation using Finite Element Analysis (FEA). Applications in this study such as medical implants and embedded sensors in buildings and similar structures are just a few of many examples.